Emission stability of a diamond-like carbon coated metal-tip field emitter array - Jung, JH; Ju, BK; Lee, YH; Jang, J; Oh, MH (AMER INST PHYSICS, 1999)
The emission stability of Mo-tip field emitter arrays (FEAs) has been improved. The effect of diamond-like carbon (DLC) films deposited using a layer-by-layer technique using plasma enhanced chemical vapor deposition on the electron emission characteristics of Mo-tip FEAs was examined. The turn-on voltage was lowered from 80 V for Mo-tip FEAs to 65 V for DLC-coated Mo-tip FEAs, and the maximum emission current increased from 140 mu A for Mo-tip FEAs to 320 mu A for DLC-coated Mo-tip FEAs composed of 900 emitters. An anode current for DLC-coated Mo-tip FEAs and Mo tip of 0.1 mu A per emitter was measured at gate voltages of about 87 and 107 V, respectively. The emission current of DLC-coated Mo-tip FEAs is more stable than that of Mo-tip FEAs. (C) 1999 American Vacuum Society. [S0734-211X(99)07602-7].